Characterization of Social Status-Dependent Neuromodulation in Zebrafish (Danio rerio) - Miller, Thomas H (East Carolina University, 2017)
In zebrafish (Danio rerio), social interactions between adult males consist of a series of aggressive encounters that ultimately lead to the formation of stable hierarchies of either socially dominant or subordinate animals. Although it has been shown that social status leads to neurophysiological changes in brain structure and function, our understanding of the underlying mechanisms that control behavioral function remains limited. We show that socially dominant animals display increased swimming activity. Conversely, social Subordinates display decreased swimming activity, but an enhanced sensitivity of the C-start escape circuit. We also show that whole brain expression of dopamine transporter (DAT) was significantly up-regulated in Dominants compared to Subordinates. In addition, Dopamine 1 receptor (D1R) expression was down-regulated in Subordinates compared to Dominants, suggesting that there is a social-status dependent regulation of the dopaminergic (DA) system. Finally, we show that visual cues play an important role in regulating zebrafish dominance relationships and the prioritization of different motor outputs by using a zebrafish line lacking pigmentation. Taken together, our results reveal that neuromodulation by DA signaling and visual information provides a mechanism for the nervous system to adapt to changes in social conditions by permitting the animal to prioritize a socially appropriate behavioral response.
Keywords: behavior; neuromodulation; visual cues; Zebra danio; Social hierarchy in animals; Dopamine--Receptors